La riscrittura compartecipata: esempi in ambito giuridico-amministrativo (Altre Modernità, 2012)
In the past few decades, public and private institutions have become more aware of the fact that citizens and consumers need to receive intelligible and personalized information and that, therefore, the speaker or writer necessarily needs to deliver communication that the public can understand, relate to and use. The present paper focuses on a number of texts drawn from French speaking countries, in which the potential recipients of a specific text have been part of the rewriting process involving the editing of the text. The texts considered give the opportunity to observe edited texts belonging to various fields (public administration, public health and law), s and different genres: administrative blank forms, pharmaceutical inserts, legislative or constitutional discourse (the Constitution of Switzerland, the French Labor code). The contribution reveals how the addressees have been involved in rewriting process and identifies the linguistic aspects they have taken into consideration. In particular, we focus on plain language and gender identity.